2020
DOI: 10.21203/rs.3.rs-16941/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overexpression of HOXA10 is associated with unfavorable prognosis of acute myeloid leukemia

Abstract: Background HOXA family genes were crucial transcription factors involving cell proliferation and apoptosis. While few studies have focused on HOXA10 in AML. We aimed to investigate the prognostic significance of HOXA10. Methods We downloaded datasets from GEO and BeatAML database, to compare HOXA expression level between AML patients and controls. Kaplan-Meier curves were used to estimate the impact of HOXA10 expression on AML survival. The differentially expressed genes, miRNAs, lncRNAs and methylated reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
(55 reference statements)
2
5
0
Order By: Relevance
“…As previously described, miR-16-5p played a tumor-suppressing effects to slow down cancer progression [19][20][21], including GC [22][23][24], which evidenced the opposite effects of LINC00649 and miR-16-5p in regulating GC development. Thus, we performed further gain-and loss-of-function experiments, and expectedly found that knockdown of LINC00649 suppressed GC pathogenesis via releasing miR-16-5p, which were partially supported by the previous publications [10][11][12][13][22][23][24].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As previously described, miR-16-5p played a tumor-suppressing effects to slow down cancer progression [19][20][21], including GC [22][23][24], which evidenced the opposite effects of LINC00649 and miR-16-5p in regulating GC development. Thus, we performed further gain-and loss-of-function experiments, and expectedly found that knockdown of LINC00649 suppressed GC pathogenesis via releasing miR-16-5p, which were partially supported by the previous publications [10][11][12][13][22][23][24].…”
Section: Discussionsupporting
confidence: 76%
“…Although emerging data suggested that targeting LncRNAs was effective to hamper cancer progression and improve drug-resistance in GC, and multiple LncRNAs had been identified as diagnostic, therapeutic and prognostic biomarkers for GC, the involvement of a novel LncRNA LINC00649 in regulating GC pathogenesis had not been studied. Based on the information provided by the previous literatures, LINC00649 acted as an oncogene to facilitate the development of acute myeloid leukemia (AML) [10,11], prostate cancer [12] and colorectal cancer [13], but it was still unclear whether LINC00649 modulated GC progression in a similar manner. Hence, by conducting clinical and preliminary experiments, this study assured that LINC00649 also exerted its tumor-promoting effects in GC, which were in consistent with the previous publications in other types of cancers [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LINC00649, which we focused in the research, was identified as a prognostic marker in prostate and colorectal cancers by previous bioinformatic analysis [12,13]. Few studies have investigated the prognostic value of LINC00649 in AML [14]. Notably, the expression of LINC00649 was significantly correlated with HOXA family genes, indicated by the results derived from GEPIA [15] 2.0 online tools (http://gepia2.cancer-pku.cn/) and our own analysis.…”
Section: Introductionmentioning
confidence: 87%